2013
DOI: 10.1364/ol.38.002855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gold nanoparticles on depolarization characteristics of Intralipid tissue phantom

Abstract: We report results of studies on the effect of different shapes and sizes of gold nanoparticles (GNPs) on the depolarization characteristics of Intralipid tissue phantoms. For a given extinction coefficient, the absorption characteristics of the GNPs contributed more to the depolarization of the turbid medium, and the contribution of scattering was significant only for the larger-sized particles. For rod-shaped GNPs, their depolarization plays an important role in the low scattering regime in which the depolari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Considering the intriguing scope of the polarimetric technique for in vivo clinical diagnosis, beside the simulations, there is a need for complex phantoms, such as those exhibiting birefringence (see Fig. 7b (iii)) or depolarisation, to establish reliable processes for investigation of complex scattering mechanisms 270 , 271 . A recent review has summarised various phantoms for both thin and bulk samples 152 .…”
Section: Vectorial Information Analysis For Biomedical Applicationsmentioning
confidence: 99%
“…Considering the intriguing scope of the polarimetric technique for in vivo clinical diagnosis, beside the simulations, there is a need for complex phantoms, such as those exhibiting birefringence (see Fig. 7b (iii)) or depolarisation, to establish reliable processes for investigation of complex scattering mechanisms 270 , 271 . A recent review has summarised various phantoms for both thin and bulk samples 152 .…”
Section: Vectorial Information Analysis For Biomedical Applicationsmentioning
confidence: 99%
“…For Intralipid tissue phantoms, it was demonstrated that at a given extinction coefficient, the absorption of the GNPs contributes more to the depolarization of the turbid medium. 267 The GNP scattering is significant only for the larger-sized particles. The depolarization of GNPs dominates in the low-scattering phantoms.…”
Section: Nanoparticle Enhancement Of Contrast Of Polarized Light Micrmentioning
confidence: 99%
“…69 While intralipid suspension exhibits monotonic dependence of depolarization on light wavelength, the use of gold nanoparticles (GNPs) suspended in intralipid creates more complicated depolarization behavior. 90 Titanium dioxide (TiO 2 ) is another material commonly used to produce scattering in optical phantoms. TiO 2 particles have been used in solid host media, such as polydimethylsiloxane or polyurethane, where, before the curing process, these particles are mixed into the polymer.…”
Section: Depolarizing Phantomsmentioning
confidence: 99%